Wiley Encyclopedia of Electrical and Electronics Engineering 2014
DOI: 10.1002/047134608x.w8227
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Power Splitters

Abstract: This article summarizes recent advances in the art of power splitter designs. Diverse design concepts and techniques proposed in recent years are introduced, mainly focusing on the out‐of‐phase power splitters, in‐phase power splitters, filtering power splitters, and high‐power waveguide power splitters. Because of the popularity of balanced circuits, out‐of‐phase power splitters are heavily demanded. The double‐sided parallel‐strip lines (DSPSLs), with the frequency‐independent out‐of‐phase characteristics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…1(a), which leads to a large overall component size. It has been found that BPFs can be designed to integrate with the power dividers [15]- [17], power amplifiers [18], and antennas [19] for miniaturization. Similarly, the bandpass filtering function can also be combined with the hybrid, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1(a), which leads to a large overall component size. It has been found that BPFs can be designed to integrate with the power dividers [15]- [17], power amplifiers [18], and antennas [19] for miniaturization. Similarly, the bandpass filtering function can also be combined with the hybrid, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%